O governo dos homens na contemporaneidade: laicização do poder e subjetivação massificante - Barbosa, Aelton Leonardo Santos (2012)
The objective is to determine the manner in which government of men is exercised in contemporary society. Nowadays, nations are organized according to the structure of liberal democracy, a late formation of the liberal discursive practice. Searching for contemporary liberal governmentality specificity, the text makes use of the genealogical method, thus breaking research on provenance and emergence of the object of study. Relying on the analysis of Friedrich Nietzsche and Michel Foucault - respectively, founder and improver of genealogical critique – it verifies what appear to unify its research hypotheses: first, the idea that power as exercised in modernity is the displacement and secularization of a originally religious natured relationship, and secondly, the assertion that, the historically identifiable process of subjects production, is a massification process; modernity would be marked, in an apparent paradox, by the fact that it has a massifying subjectification. The two genealogist philosophers express these theses with the complementary concepts of "herd morality", in the German case, and "pastoral power", in the French case, which refer respectively to the formation of the individual's psychological type of modernity and the incidence mechanisms of power over the bodies subject to it. Foucault notes, however, that in contemporaneity a transmutation of state power which took the model of political economy has changed the general outline of governmentality, from a normalization of the bodies to a regulation of populations: it is the dawn of biopolitics and liberal governmentality. Futhermore, recent decades seem to define itselves by the actual enrollment in new discursive practices, that from the human capital theory and also an update of the homo economicus concept, which only renew Nietzschean diagnosis of the "last man" hegemony